Quality of Hungarian clover (Trifolium pannonicum Jacq.) seeds of Snezhok variety - E. V. Popova; E. G. Arzamasova; I. V. Shihova (Аграрная наука Евро-Северо-Востока, 2022)
The article presents the results of many years of research (2011-2021) on determining the quality of Hungarian clover (Trifolium pannonicum Jacq.) seeds of Snezhok variety obtained in the conditions of Kirov region (North-East of the European part of Russia). The weight of 1000 seeds averaged 4.16 g with changes over the years from 3.83 to 4.60 g and depended on the amount of precipitation (r = 0.71), the hydrothermal coefficient during the flowering period of grass stands (r = 0.69), average daily and daytime air temperatures during the "flowering-the beginning of maturation" period (r = -0.70). On average, the length of the seeds was 2.45 mm, width – 1.93 mm; thickness – 1.40 mm. According to the ratio of these parameters, the seeds had an ovoid and ellipsoid (elongated) shape. The size of the seed material (integral indicator) did not exceed 2.0 mm. In years with greater moisture availability (98-189 % to the norm) large seeds were formed (from 1.92 to 2.00 mm), with insufficient moisture (64-81 %) ‒ small seeds (1.78 mm). According to the initial germination indicators, all seed material met the requirements of GOST R 52325-2005 and was classified as "original seeds". Germination and germinating energy were 86.7-99.5 and 80.0-97.0 %, respectively, they depended on the average daily air temperature during the "budding-seed ripening" period (r = 0.66 and 0.68) and remained at a high level for the first three to four years of storage. The seed material had mainly a low content of hard seeds (1.5-7.0 %). In some years, the "hard-seeding" of freshly harvested seeds reached 20.0-36.0%, however, after the post-harvest ripening period, it significantly decreased. The freshly harvested seeds had a yellow color, which gradually changed to beige-brown or brown-beige during storage. Regression analysis showed a strong relationship between the color of seeds of different storage periods and germination rates. The presence of a large number of yellow seeds in the batch indicated to their high germinating energy (r = 0.98) and germination (r = 0.95). the predominant content of brown seeds indicated to the loss of seed sowing qualities (r = -0.94 and r = -0.91, respectively).